Os dias de Bagdad - Gonçalo Rosa da Silva (Verbo, 2004)
Testemunhos de: Cândida Pinto, Carlos Fino, Elmano Madaíl, Emídio Fernando, Henrique Botequilha, João Pedro Fonseca, Luís Castro, Pedro Sousa Pereira.